An Investigation of the Effect of Transfected Defective, Ebola Virus Genomes on Ebola Replication - Smither, Sophie J.; Garcia-Dorival, Isabel; Eastaugh, Lin; Findlay, James S.; O'Brien, Lyn M.; Carruthers, Jonathan; Williamson, E. Diane; Molina-París, Carmen; Hiscox, Julian A.; Laws, Thomas R. (Frontiers in Cellular and Infection Microbiology, 2020)
As the ongoing outbreak in the Democratic Republic of Congo illustrates, Ebola virus disease continues to pose a significant risk to humankind and this necessitates the continued development of therapeutic options. One option that warrants evaluation is that of defective genomes; these can potentially parasitize resources from the wild-type virus and may even be packaged for repeated co-infection cycles. Deletion and copy-back defective genomes have been identified and reported in the literature. As a crude, mixed preparation these were found to have limiting effects on cytopathology. Here we have used synthetic virology to clone and manufacture two deletion defective genomes. These genomes were tested with Ebola virus using in vitro cell culture and shown to inhibit viral replication; however, and against expectations, the defective genomes were not released in biologically significant numbers. We propose that EBOV might have yet unknown mechanisms to prevent parasitisation by defective interfering particles beyond the known mechanism that prevents sequential infection of the same cell. Understanding this mechanism would be necessary in any development of a defective interfering particle-based therapy; however, may also provide a druggable target to disrupt normal viral replication.